THE RISK OF CORONARY ARTERY DISEASE DEVELOPMENT IN PATIENTS WITH ANKYLOSING SPONDYLITIS (BECHTEREW’S DISEASE) AND PSORIATIC ARTHRITIS: A 10-YEAR PROSPECTIVE FOLLOW-UP STUDY - I. Z. Gaidukova; A. P. Rebrov (Klinicist)
Objective: assessment of coronary artery disease (CAD) incidence among patients with ankylosing spondylitis (AS) and psoriatic arthritis (PsA) without manifestation of cardiovascular diseases.Materials and methods. We analyzed the data of 10-year prospective follow-up of the patient with AS (n = 278), psoriatic arthritis (n = 85) and healthy controls (n = 150) without any cardiovascular diseases. All groups were comparable in regard to cardiovascular risk factors. During these 10 years all new cases of CAD (verified by cardiologist) in the study population were tracked.Results. New cases of CAD were fixed in 64 out of 278 patietns with AS and in 16 out of 150 controls (p = 0.0017). Using log-rank MantelCox test and logrank test for trend we demonstrated statistically significant differences in CAD incidence between patients without spondyloarthritis (SpA) and patients with AS and PsA (p < 0,0001). The risk of CAD development was higher in PsA group than in the control group; relative risk was 4.16 (95 % confidence interval (CI) 2.36–7.33), RR 6.1 (95 % CI 3.05–12.44) (p < 0.05). Increased risk of myocardial infarction was observed both in patients with AS (RR 4.98; 95 % CI 1.54–6.12) and patients with PsA (RR 5.2; 95 % CI 2.4–7.8) comparing to healthy controls. There was no significant difference between the AS-group and the control group in terms of risk of stenocardia development (p > 0.05).Conclusion. The risk of exertional stenocardia in patients with AS was not higher than that in individuals without SpA. However, patients with AS have higher risk of myocardial infarction than those without SpA. PsA patients have increased risk of CAD development comparing to healthy controls and individuals with AS.